Zn uptake behavior of rice genotypes and its implication on grain Zn biofortification - Johnson-Beebout, Sarah E.; Goloran, Johnvie Bayang; Rubianes, Francis H. C.; Jacob, Jack D. C.; Castillo, Oliver B. (Springer, 2016)
Understanding Zn uptake dynamics is critical to rice grain Zn biofortification. Here we examined soil Zn availability and Zn uptake pathways as affected by genotype (high-grain Zn varieties IR69428 and IR68144), Zn fertilization and water management in two pot experiments. Results showed significant interactions (P < 0.05) between genotypes and Zn fertilization on DTPA (diethylenetriaminepentaacetic acid)-extractable soil Zn from early tillering to flowering. DTPA-extractable Zn in soils grown with IR69428 was positively correlated with stem (r = 0.78, P < 0.01), flagleaf (r = 0.60, P < 0.01) and grain (r = 0.67, P < 0.01) Zn concentrations, suggesting improved soil Zn availability and continued soil Zn uptake by IR69428 even at maturity. Conversely for IR68144, DTPA-extractable Zn was positively correlated only with leaf Zn uptake (r = 0.60, P < 0.01) at active tillering, indicating dependence on remobilization for grain Zn loading. Furthermore, the highest grain Zn concentration (P < 0.05) was produced by a combination of IR69428 and Zn fertilization applied at panicle initiation (38.5 μg g−1) compared with other treatments (P < 0.05). The results highlight that Zn uptake behavior of a rice genotype determines the fate of Zn from the soil to the grain. This has implications on overcoming Zn translocation barriers between vegetative parts and grains, and achieving grain Zn biofortification targets (30.0 μg g−1).